Pengaruh Disonansi Kognitif Terhadap Perilaku Pembelian Konsumen - Dadang Karya Bakti; Winda Septiani; Kade Putri Ardani; Suprihatin Ali (Terekam Jejak Publisher, 2024)
This study aims to analyze the factors that influence cognitive dissonance theory on consumer behavior towards purchasing luxury products. According to cognitive dissonance theory, a person will experience dissonance when there is a mismatch between their thoughts, beliefs, emotions, values, and attitudes. This study collected data from luxury product customers in Indonesia to assess the formation of cognitive dissonance in them using quantitative methods with 122 respondents as a sample. The data presented comes from the distribution of online questionnaires which are then analyzed using descriptive statistical methods and linear regression test forms. The research findings interpret that there is a significant influence of cognitive dissonance theory on consumer behavior in purchasing luxury products. The results of this study confirm that when consumers experience a mismatch between their thoughts, beliefs, emotions, values, and attitudes when buying luxury products, they will try to reduce the dissonance. This research provides important implications for luxury product marketers to understand consumer psychological factors, such as cognitive dissonance, and develop marketing strategies that can help increase customer satisfaction and loyalty.